2021
DOI: 10.1002/clt2.12043
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic trends in skin barrier function from birth to age 6 months and infantile atopic dermatitis: A Chinese prospective cohort study

Abstract: Background: Skin barrier functions develop after birth and may be related to skin disorders in infants. We aimed to assess associations between dynamic trends of four skin barrier functional parameters in early life with infant atopic dermatitis (AD). Methods:Based on the prospective cohort MKNFOAD (NCT02889081), we examined transepidermal water loss (TEWL), stratum corneum hydration (SCH), skin pH, and sebum content at five anatomical sites (cheek, forehead, forearm, abdomen, and lower leg) in 418 term infant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
(77 reference statements)
1
13
0
Order By: Relevance
“…Impaired skin barrier function and increased TEWL have been documented as predictors of early-onset infant AD. 1,[8][9][10] Based on a small birth cohort (n = 19 mother-infant pairs), M. Mina mi-Hori et al reported that the total CERs and EOS, EOH, and EOP in diaper-covered buttocks and inner upper thighs skin quickly increase in the first month of life and decline afterward until 1 year old and were in line with the transition in mothers. 13 A recent cross-sectional study in healthy Chinese infants found higher total CER in the upper arms, cheek, and buttocks of infants aged 2-12 months than in those aged 13-24 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Impaired skin barrier function and increased TEWL have been documented as predictors of early-onset infant AD. 1,[8][9][10] Based on a small birth cohort (n = 19 mother-infant pairs), M. Mina mi-Hori et al reported that the total CERs and EOS, EOH, and EOP in diaper-covered buttocks and inner upper thighs skin quickly increase in the first month of life and decline afterward until 1 year old and were in line with the transition in mothers. 13 A recent cross-sectional study in healthy Chinese infants found higher total CER in the upper arms, cheek, and buttocks of infants aged 2-12 months than in those aged 13-24 months.…”
Section: Discussionmentioning
confidence: 99%
“…A Tewameter TM300 probe was placed on the inner forearm and remained in contact with the skin surface for 20 s. The average of five-second readings within a 0.2 unit variation was recorded. 8 Prior to the assessment, infants were given at least 15 min to acclimatize in a controlled environment. If infants were crying or sweating during the…”
Section: Follow-up Examinations and Assessment Of Infant Admentioning
confidence: 99%
See 2 more Smart Citations
“…It is one of the most common health problems and affects 2.1%–4.9% of human population worldwide [ 2 ]. Meanwhile, the morbidity of atopic dermatitis is high in both developing countries and developed countries [ 3 , 4 ]. Atopic dermatitis is characterized by rash, erythema, edema, hemorrhage, lichenification, and severe itching, and it is always accompanied by destruction in skin barriers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%